Effect of Fibrin Glue or Suture on Leakage in Patients Undergoing Laparoscopic Sleeve Gastrectomy - Usta, S.; Karabulut, K. (Wolters Kluwer Medknow Publications, 2018)
Introduction: Sleeve gastrectomy represents one of the most common surgical procedures used in bariatric surgery. The most feared complication following laparoscopic sleeve gastrectomy (LSG) is the leak that occurs at the staple line. One method to reduce the risk of leak is the use of reinforcement material at the suture line. In this study, the efficacy of sutures and fibrin glue in the prevention of staple leak has been compared retrospectively. Methods: A total of 250 patients undergoing LSG between October 2011 and August 2015 at the Medical Faculty of Firat University were retrospectively assessed using the hospital database system records. Results: There were 77 males (31%) and 173 (69%) females, with a mean age of 34 years (range: 16-65 years) and mean body mass index of 45 kg/m(2). Staple line was sutured in 54 patients (22%). Neither suture nor fibrin glue was used for reinforcement of the staple line in 61 (24%) patients. Only fibrin glue was used for the reinforcement of the staple line in 135 (54%) patients. Postoperative leak occurred in eight patients (3.2%). Neither suture nor fibrin glue was used for reinforcement in 6 (9.8%) of these patients. One of them was in sutured staple line group and the other was in fibrin glue group (0.7%). One patient died due to leak and the consequent development of sepsis (0.4%). Conclusion: Despite some controversies, strong evidence exists on the effectiveness of fibrin glue in the prevention of leaks in patients undergoing LSG from this study.
Keywords: Fibrin glue; leak; sleeve gastrectomy